Hipoksična soba v Ratečah - Vrhovec, Bogomir (Medicinski razgledi, 2002)
Acclimatisation to altitude may be achieved by intermittent exposure to hypoxia in a hyperbaric chamber or by inhaling a hypoicic gas mixture under normobaric conditions. We describe the development of a hypoxic room based on the latter principle. A nitrogen generator based on the vacuum pressure swing adsorption principle reduces the oxygen content of air to 5%. The resultant gas mixture containing 95% nitrogen is pumped into a sealed apartment. The level of oxygen in the appartment is monitored continuously and cannot fall below 11%. Should it fall below a preset value, the nitrogen generator is switched off, closely followed by the activation of fan to transport external air into the apartment. An audible alarm is also activated. The hypoxic room has been successfully used by athletes prior to attending the Sa1t Lake City Olympic games and by alpinists prior to high altitude expeditions.
Keywords: hipoksija; fiziologija; nadmorska višina; aklimatizacija; hipoksična soba